Microplastics in beach sediments and cockles (Anadara antiquata) along the Tanzanian coastline - Mayoma, Bahati S.; Sørensen, Christina; Shashoua, Yvonne; Khan, Farhan R. (Bulletin of environmental contamination and toxicology, 2020)
Little is known about the prevalence of microplastics (MPs) in East Africa. In the present study, sediments were sampled at 18 sites along the Tanzanian coast that exhibit different levels of anthropogenic activity and were extracted using floatation methodology. Cockles ( Anadara antiquata ) were collected only from eight sites and MPs were extracted following NaOH digestion. MPs were most abundant at Mtoni Kijichi Creek (MKC, 2972 ± 238 particles kg −1 dry sediment), an industrial port in Dar es Salaam, and significantly higher than all other sites where the abundance range was 15–214 particles kg −1 dry sediment ( p < 0.05, one-way ANOVA). Fragments and fibers were found at all sites. Polypropylene and polyethylene were identified polymers. MPs were found in cockles from all sampled sites with both frequencies of occurrence and MPs per individual subject to site-specific variation. This study provides a baseline of MP data in a previously uninvestigated area.